Norway’s electric vehicle revolution: unveiling greenhouse gas emissions reductions and material use of passenger cars across space and time - Lola S A Rousseau; Jan Sandstad Næss; Marine Lhuillier; Romain G Billy; Peter Schön; Edgar G Hertwich (Environmental Research Letters, 2025)
Electric vehicles (EVs) are a key strategy for mitigating greenhouse gas (GHG) emissions from personal mobility. Norway’s strong EV supporting policies has led to an explosion of EVs and reduced direct emissions, but with rural-urban differences and undocumented upstream impacts. We investigated how the material composition and life cycle GHG emissions of Norwegian vehicles have evolved between 2000 and 2023 by integrating spatiotemporal vehicle data with a vehicle life cycle assessment model. The average life cycle GHG emissions per vehicle-km (vkm) of a newly registered car have significantly decreased (−49% since 2000) thanks to the decrease in use phase emissions (−89% since 2000). However, component-related emissions have increased (+81% since 2000) due to electrification and a trend towards large vehicles. Changes in the fleet are slow: EVs constituted 24% of the stock in 2023 and average life cycle GHG emissions per vkm have barely declined (−8% since 2000). EVs are concentrated in urban and peri-urban areas, while remote areas have few EVs, illustrating the unequal spatial distribution of electric mobility. Our study highlights the challenges related to EV penetration and emphasizes the need to expand to additional indicators beyond direct GHG emissions for a comprehensive understanding of EVs’ role in climate change mitigation.